Cutaneous Lymphoid Infiltrates Simulating Cutaneous Lymphoma - Teixeira, Ana Isabel (2016)
Cutaneous pseudolymphoma refers to a heterogenous group of dermatosis which simulates cutaneous malignant lymphomas clinically and/or histopathologically. There are no diagnostic criteria to differentiate reactive from neoplastic infiltrates. Cutaneous pseudolymphoma can be divided into T- and B-cell variants depending on the predominant cell type in the infiltrate or classified according to the specific malignant lymphoma they simulate. This paper attempts to discuss the clinical and histological clues that are most relevant to the discrimination of lymphoma simulators from the true cutaneous lymphoma.